Status of Wetland Governance in Lake Cluster of Pokhara Valley: A case study of the Phewa, Begnas, and Rupa Lakes - Sigdel, Krishna Prasad; Ghimire, Narayan Prasad; Karki, Madhav Bahadur; Dawadi, Binod; Dawadi, Binod; Shrestha, Pabin (Journal of Environment Sciences, 2025)
This study examines the status of the governance of Phewa, Begnas, and Rupa Lakes of Pokhara valley in Gandaki province, Nepal. These lakes constitute the Ramsar designated lake cluster site. The assessment of wetland governance was done through a comprehensive literature review, focus group discussion and key informant interview of representatives from 13 governmental and non-governmental organizations. Using the Integrated Lake Basin Management framework of the International Lake Environment Committee, the study evaluates governance based on six pillars: Institution, Policy, Participation, Information, Technology, and Finance. A governance assessment matrix with 10 indicators was used to score these pillars on a scale from 1 (lowest) to 7 (best). The study findings indicate that governance in these lakes is generally weak (low), except for the Institution and Policy pillars, which scored higher but fell in average scale. Among the three lakes, Rupa Lake had the highest governance score, while Technology, Information, and Finance were the weakest pillars across all lakes. There is no designated strong agency responsible for Ramsar site management in provincial level, although the Ministry of Forest and Environment, Gandaki Province has authorized the Lake Conservation and Development Authority to address wetland issues. Community-led Lake Resources Cooperatives have contributed to environmental improvements and provisional services. However, wetland area and biodiversity loss remain a concern. Additionally, weak coordination among provincial and local government agencies hinders effective governance. Strengthening institutional coherence, better enforcement of rules and regulations and consolidating efforts across agencies and stakeholders are necessary to improve governance and ensure sustainable wetland management in the future.